Death and suicide in Elzenberg’s philosophy - Kasperek, Anna (Hybris, 2016)
The questions of death and suicide have been discussed in philosophy and religion since the antiquity. In the polish philosophy these topics were analyzed by Henryk Elzenberg. His pessimistic point of view was determined by poetry of Leonte de Lisle. Elzenberg took inspirations also from Buddhist thought and existential philosophy. According to Elzenberg, the death is liberation from the body prison. He accepted individual suicide. Suicide is a kind of a social watchman, last institution where suffering man can find his support.